2021
DOI: 10.31139/chnriop.2020.86.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in microsurgical education – review of types of training and skill assessment instruments

Abstract: Microsurgery became an essential part of various specialties. Hand replantation, vascular free flap reconstruction, and cerebral bypasses are impossible to conduct without mastering microsurgical skills. Currently, the gold standard of microsurgical training is the course with living models during which participants perform basic microsurgical procedures under the supervision of an experienced tutor. However, due to high cost of training and ethical issues new training models, which reduce the usage of living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…3,6,[12][13][14][15] Several studies have described affordable and effective simulation systems on the basis of the use of nonliving animal models, such as a chicken leg and porcine kidney as well as synthetic models, such as silicone tubes, rubber gloves, or gauze. 14,[16][17][18][19][20] Moreover, Grober et al reported similar performance between novices trained on nonliving models and those trained on living rat model. 21 Lascar et al and Hui et al reported that repetitive microsurgical training significantly improves technical skills, reaching the level of experienced microsurgeon after a certain amount of anastomosis and reaching a plateau after performance of 25 anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…3,6,[12][13][14][15] Several studies have described affordable and effective simulation systems on the basis of the use of nonliving animal models, such as a chicken leg and porcine kidney as well as synthetic models, such as silicone tubes, rubber gloves, or gauze. 14,[16][17][18][19][20] Moreover, Grober et al reported similar performance between novices trained on nonliving models and those trained on living rat model. 21 Lascar et al and Hui et al reported that repetitive microsurgical training significantly improves technical skills, reaching the level of experienced microsurgeon after a certain amount of anastomosis and reaching a plateau after performance of 25 anastomoses.…”
Section: Discussionmentioning
confidence: 99%